(untitled) (Transport systems and technologies, 2024)
The ways of updating the rolling stock of open-pit railways have been considered and the main methods of using the energy storage on the locomotive for open-pit railways have been determined. A mathematical model has been developed, which includes a model of train movement along the railway section and during maneuvering and a model of energy processes in the traction system with onboard energy storage. Simulations were performed in a cycle that included movement from the crushing plant to the transshipment point with empty dump trucks, maneuvering during loading, movement from the crushing plant to the transshipment point with loaded dump trucks, and maneuvering during unloading. The simulation took into account the limitation of power consumption at the level of 4000 kW. The parameters of the energy storage device were determined, for which Toshiba SCiB 20Ah-HP cells were selected. The power of the energy storage is 3600 kW, and the energy capacity is 414 kWh. The use of modules for the formation of an energy storage device is proposed. It was determined that the energy consumption per work cycle with the selected energy exchange algorithm taking into account electrodynamic braking is about 200 kWh, and the charge reduction per drive cycle is 36%. The service life of the energy storage with the selected cells is estimated at 8 years.